Functional outcomes and complications of simultaneous bilateral total hip arthroplasty in Asian population - Meena, Ram Prasad; Shetty, Utsav; Bhishnoi, Sadaram; Meena, Ramkhiladi (International Journal of Research in Orthopaedics, 2020)
Background: Total hip arthroplasty (THA) is one of the most successful and cost-benefit surgical treatments. However, there are concerns about the safety of the procedure and higher complications. We aimed to evaluate the complications and outcomes of one-stage bilateral total hip arthroplasty (BTHA) with anterolateral approach. Methods: A total of 24 patients from February 2014 to October 2019 underwent BTHA in Government Medical College and Attached Group of Hospitals, Kota. A prospective analysis of the functional outcomes and complications was performed. All surgeries were performed via anterolateral approach. All patients were followed up till 1.5 years post-operative. Results: During period of study 16 men and 8 women with a mean age of 40.12±2.52 years at the time of presentation were entered. The mean surgical time was 112±6 mins. The mean hospital stay was 7 days. Hemoglobin level decreased significantly after operation (p=0.046) mean of 10.83±0.3 mg/dl. There was no reported patient with perioperative death, deep venous thrombosis, pulmonary embolism, infection, dislocation, periprosthetic fracture or heterotrophic ossification. The mean preoperative MHHS score was 45.93±5.33 in patients. MHHS score improved to 92.06±2.47 in the last follow-up (p=0.0001). Conclusions: Our results recommend the use of one-stage BTHA through anterolateral approach in cases indicating bilateral THA without increase in rate of complications. Functional and clinical outcomes are comparable and hospital stay is significantly shorter.